Hoax practices behind TikTok fake accounts in the 2024 presidential election contest - Genta Tabah Ramadhan; Modesta Roganda Siboro; Mukarto Siswoyo; Khaerudin Imawan (International Journal Labs, 2024)
In the context of rising misinformation on social media, this study examines the influence of hoaxes spread through fake TikTok accounts on public opinion during Indonesia's 2024 presidential election. The study aims to analyze how fake accounts, including notable examples like @ridwanyulio and @sendycahyani1744, leverage hoaxes to sway political perceptions, undermine trust in democratic processes, and foster social division. Using a qualitative approach, data was collected through observational analysis of comments, engagement, and content shared by these accounts. The data was then analyzed to explore patterns of misinformation, strategies used to manipulate narratives, and the resulting public impact. Findings indicate that these accounts employ targeted and organized hoax tactics, utilizing edited videos and images to propagate misleading narratives. The study concludes that such hoaxes pose a threat to information integrity, potentially leading to increased polarization and conflict. The implications of this research highlight the need for robust media literacy programs, stricter platform regulations, and collaborative efforts among stakeholders to combat misinformation, thereby supporting a healthier democratic environment.